2002
DOI: 10.1074/jbc.m111480200
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Monophosphoramidase Activity of Hint and Hnt1 Supports Function of Kin28, Ccl1, and Tfb3

Abstract: The histidine triad superfamily of nucleotide hydrolases and nucleotide transferases consists of a branch of proteins related to Hint and Aprataxin, a branch of Fhitrelated hydrolases, and a branch of galactose-1-phosphate uridylyltransferase (GalT)-related transferases. Although substrates of Fhit and GalT are known and consequences of mutations in Aprataxin, Fhit, and GalT are known, good substrates had not been reported for any member of the Hint branch, and mutational consequences were unknown for Hint ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
166
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(168 citation statements)
references
References 62 publications
2
166
0
Order By: Relevance
“…One possibility is the HINT enzymes have adenylated proteins as substrates, although the potential ligands of HINT and subsequent reactants remain unknown. A loss of HINT activity restricted growth rate in yeast (19,21,23,24). Thus, a 35% reduction in HINT1 enzyme mRNA in neurons in cortical layer VI (21% decrease in layers II-V) might be the result of abnormal cell transcription, although results in yeast leading to alterations in cell growth rate do not translate into alterations in the growth of neurons that are terminally differentiated cells.…”
Section: Hint1mentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is the HINT enzymes have adenylated proteins as substrates, although the potential ligands of HINT and subsequent reactants remain unknown. A loss of HINT activity restricted growth rate in yeast (19,21,23,24). Thus, a 35% reduction in HINT1 enzyme mRNA in neurons in cortical layer VI (21% decrease in layers II-V) might be the result of abnormal cell transcription, although results in yeast leading to alterations in cell growth rate do not translate into alterations in the growth of neurons that are terminally differentiated cells.…”
Section: Hint1mentioning
confidence: 99%
“…However, no grossly observable deficiencies were noted in hint Ϫ/Ϫ mice, suggesting that other redundant genes can functionally compensate (20). HINT enzyme homologues hydrolyze adenosine-5Ј-monophosphoramidate (AMPNH 2 ) to AMP plus the leaving NH 2 group (19,21). HINT enzyme activity is a positive regulator of Kin28, the human homologue is CDK7 (21).…”
Section: Hint1mentioning
confidence: 99%
See 1 more Smart Citation
“…Specific substrates for rabbit Hint and its yeast ortholog, Hnt1, emerged alongside physiological assays for the yeast HNT1 gene (17). While deletion of hnt1 was tolerated by haploid yeast cells on glucose media at all temperatures and deletion of hnt1 did not lead to a galactose-phenotype at 30 °C, hnt1 deletion produced cells that are galactose-at 38-39 °C.…”
Section: Hint and Hnt1 Are Enzymes With Adenosine 5′-monophosphoramidmentioning
confidence: 99%
“…Just as yeast Hnt1 enzyme activity was destroyed by the H116A mutation, so the hnt1-H116A allele was without function in supporting growth of yeast cells on galactose at 39 °C. Because the Hnt1-H116A protein is not unstable, it was concluded that hydrolysis of an Hnt1 substrate is required for growth of yeast cells at 39 °C (17).…”
Section: Hint and Hnt1 Are Enzymes With Adenosine 5′-monophosphoramidmentioning
confidence: 99%